Echocardiographic Changes in Patients with Chronic Obstructive Pulmonary Disease in a Study of Indian Population (Indian Journal of Public Health Research & Development, 2020)
Background: Chronic obstructive pulmonary disease (COPD) is a significant risk factor of cardiovascularmorbidity and mortality including tricuspid regurgitation (TR), right ventricular hypertrophy (RVH), leftventricular dysfunction (LVD) and right atrial enlargement (RAE) among others. Echocardiography is arapid, non-invasive, and accurate method to evaluate cardiac functions and used to diagnose cardiac changesin COPD patients. This study aimed to assess the prevalence of echocardiographic changes in COPD patientsand its association with disease severity, duration of disease and smoking.Methods: Two hundred thirty four patients of COPD fulfilling the inclusion criteria coming to RespiratoryClinic and Medicine OPD of Assam Medical College and Hospital were recruited. They were evaluatedby echocardiography. Adjusted odd ratios (ORs) (adjusted to age, gender and BMI) with 95% CIs ofechocardiographic changes were computed for different stages of GOLD standard using multiple logisticregression with GOLD stage I as reference. Test for trend was done using chi-square test and statisticalsignificance was taken p-value
Keywords: COPD, echocardiography, echoabnormalities, odd ratios